Severe protein S deficiency associated with heterozygous factor V Leiden mutation in a child with purpura fulminans - Dogan, Y; Aygun, D; Yilmaz, Y; Kanra, G; Secmeer, G; Besbas, N; Gurgey, A (Taylor & Francis Inc, 2003)
Homozygous or compound heterozygous protein S (PS) deficiency is very rare in the population; only 8 patients from 6 different families have been reported. On the other hand, the factor V Leiden (FVL) mutation is a frequent cause of inherited prothrombotic disorder. Here the authors report a case of patient with severe PS deficiency associated with the FVL mutation who has had purpura fulminans since the age of 10 days. She is the first child of a consanguineous marriage. Her father is double heterozygous for PS deficiency and FVL mutation and has recurrent thrombosis. This is the first case of severe PS deficiency combined with the FVL mutation. This suggests the need for complete evaluation of patients with purpura fulminans for thrombotic factors.
Keywords: factor V Leiden; protein S deficiency; purpura fulminans